MDA‐MB‐231 and 8701BC breast cancer lines promote the migration and invasiveness of ECV304 cells on 2D and 3D type‐I collagen matrix. (15th August 2017) - Saladino, Silvia; Salamone, Monica; Ghersi, Giulio
Abstract: Tumor angiogenesis is a multiphasic process, having the extracellular matrix remodeling as critical step. Different classes of proteolytic enzymes in matrix digestion/remodeling are involved. The role of lytic enzymes and their activation mode have not been completely elucidated. Herein, the crosstalk between endothelia and tumor cells, by realization of bi‐ and three‐dimensional endothelial and breast cancer cells co‐cultures, were studied in vitro. Particularly, the effects of two tumor conditioned media (TCM) were assessed about endothelial proliferation, migration, and invasiveness. An increase in expression of pro‐MMP9 was detected when endothelial cells were cultured in the presence of both TCM; such as an up‐regulation of MMP1 and MMP14 and a down‐regulation of MMP7. Moreover the increased MMP2 gene expression from one of them and the stimulation MMP3 synthesis from the other one were observed; an increases of β3‐integrin, VEGFA, and DPP4 molecules were detected when endothelia cells are cultured with both TCM. The selection/characterization of elements present in conditioned media from breast cancer cells differently affect endothelial cells, make them potential effectors useful in breast cancer treatment.